PENDAMPINGAN PENGURUSAN IZIN EDAR PAGAN SEGAR ASAL TUMBUHAN PRODUKSI DALAM USAHA KECIL (PSAT-PDUK) UNTUK MENINGKATKAN KUALITAS NILAI JUAL PRODUK PADA PELAKU USAHA KOTA DUMAI - Mery Yanti; Ika Apia Septira; Indah Maha Sari; Nasrullah Nasrullah (Jurnal Pengabdian Kompetitif, 2026)
The ownership of distribution permits for Fresh Food of Plant Origin produced by small enterprises (PSAT-PDUK) plays an important role in improving product legality, food safety, and market competitiveness. However, most small-scale business actors in Dumai City still face difficulties in obtaining distribution permits, particularly in understanding regulations, preparing required documents, and using the Online Single Submission (OSS) system. This community service program aimed to assist small business actors in the registration process of PSAT-PDUK based on the National Food Agency Regulation Number 10 of 2025. The implementation method applied a Participatory Action Research (PAR) approach combined with technical mentoring through several stages, including regulatory socialization, document preparation workshops, OSS submission facilitation, and post-registration assistance. The target participants consisted of 15–20 small-scale fresh food business actors in Dumai City. The results showed a 68% increase in participants’ understanding of regulations and licensing procedures, indicated by the improvement of the average pre-test score from 42 to 81 in the post-test. All participants successfully prepared the required registration documents, improved product labeling designs, and obtained OSS accounts and Business Identification Numbers (NIB). A total of 15 business actors successfully submitted complete PSAT-PDUK registration applications to the Dumai City OKKPD, and most participants had obtained registration numbers by the end of the program. This mentoring program proved effective in improving the administrative capacity and digital literacy of small business actors while supporting the enhancement of legality, product quality, and market value of fresh food products in Dumai City